Mathematical Model of the Propagation of Radiation in Metal Nanoclusters - T. Yu Mogilnaya; A. M. Vasiliev; L. L. Pagawa; D. Yu Kukushkin (New Trends in Physical Science Research Vol. 4, 2022)
The material used for nanoclusters and coating has a direct impact on the qualities of superpower capacitors. The experimental evaluation of their effect is fraught with challenges. It would be interesting to adapt the authors’ approach to regulate these factors. The article focuses on a theoretical analysis of the material’s influence on coating qualities, as well as the application of the SBS approach to various types of materials. The experimental checking showed full compliance with the model calculations. As a result of the study, a convenient algorithm for predicting the effect of impurities on the probability of forming a local surface plasmon resonance (SPR) is proposed.